Towards a greener future: nursing students’ climate consciousness and green purchasing intentions - Mahitab Mohamed Abdelrahman; Reda Hassan Hussien; Ahmed Abdellah Othman; Reham Hashem; Mona Aziz Rateb (BMC Nursing)
Abstract Background Hospitals generate significant amounts of waste that can harm the environment. Nurses’ awareness and positive attitude towards green products drive them to maintain a clean environment and reduce climate change by purchasing eco-friendly products. This study assesses nursing students’ awareness and attitudes toward climate change and their correlation with the inclination to purchase green products. Method A descriptive correlational design was used for the study, covering five geographic areas in Egypt. A total of 1,400 nursing students from public universities were included in a convenience sample. Data were collected using three instruments: awareness towards climate change, attitude towards climate change, and green purchasing intentions. Results Participants demonstrated high mean scores for climate change awareness, positive attitudes, and green purchasing intentions. Geographic area and education significantly impacted participants’ climate change awareness and attitudes. Climate awareness was the strongest predictor of green purchasing intentions, with attitudes serving as a mediating factor. Conclusion A significant positive correlation exists linking climate change awareness, attitudes, and green purchasing intentions. Awareness and attitudes significantly predict green purchasing intentions. Integrating climate change education into nursing curricula can enhance awareness and sustainability behaviours, contributing to broader environmental sustainability efforts in healthcare. Practical implications Regular awareness campaigns and the integration of climate change into the university curriculum are essential. Healthcare providers, especially nurses, should promote eco-friendly behaviours, address health effects related to climate change, and educate their patients, families, and communities about climate change and green purchasing intentions.